Wear and frictional loss reduction via mechanical and laser surface texturing - Muhammad Haziq Bin Zulkarnai (Nanyang Technological University, 2023)
Surface texturing has gained significant attention in various engineering fields due to its tribological effects on materials. The process involves altering the surface topography of materials, which can potentially improve their lubrication, friction, and wear resistance properties. Such an improvement can greatly benefit the efficiency, performance, and service life of machines by reducing frictional losses and wear resistance effects. However, the optimization of surface textures varies and is dependent on the specific requirements of its applications. The two methods of surface texturing are laser surface texturing (LST) and mechanical texturing by means of deep cold rolling (DCR). LST is considered to be the most effective method of improving tribology due to its precision, time, cleanliness, and cost savings. However, LST lacks in producing other mechanical enhancements such as improved strength and wear resistance, which can be achieved through DCR. As such, experimental trials have been conducted to test the capabilities of DCR in replicating texturing patterns from LST and observing the additional mechanical improvements it has to offer. With this development, DCR has the potential to eliminate the need for a secondary process to perform further texturing, reducing cost and processing time, which is highly attractive in production industries. The material of interest in this experiment is stainless steel 304 (SS304) due to its wide application in various engineering industries. SS304 will undergo LST and mechanical texturing before comparing the results in material characterizations. The parameters and conditions for improving surface tribological performance are analyzed based on crucial tribological performance parameters, such as friction coefficient, residual stress, and roughness. Through this study, it can be determined that mechanical texturing can impart residual stresses while still maintaining a similar roughness value with LST. Further experiments can be conducted on other metallic materials with additional variables to gather more accurate and conclusive findings.